Energetic Constraints on the ITCZ Position in Idealized Simulations With a Seasonal Cycle. (31st July 2018) - Wei, Ho‐Hsuan; Bordoni, Simona
Abstract: The atmospheric energy budget has recently been shown to provide powerful constraints on the position and shifts of the zonal and annual mean intertropical convergence zone (ITCZ), which lies close to the latitude of zero vertically integrated energy transport (energy flux equator, EFE). Relatively little work has, however, explored the applicability of the energetic framework to ITCZ shifts on shorter time scales. This study investigates to what extent the EFE tracks the ITCZ on subseasonal time scales in idealized aquaplanet simulations with different mixed layer depths. It is shown that the ITCZ always lags the EFE, even in the simulation with the shallowest mixed layer depth, making it possible for the EFE and the ITCZ to reside on opposite sides of the equator. At these times, which occur as the winter cross‐equatorial Hadley circulation retreats from the summer hemisphere, the required energy balance is achieved not through shifts of the Hadley cell's ascending branch and ITCZ to track the EFE but through changes in the cell's vertical structure into one of negative gross moist stability. For any given position of the ascending branch, the winter cell is much weaker as it retreats from than as it expands into the summer hemisphere and develops a shallow return flow at middle‐to‐lower tropospheric levels where the moist static energy reaches its minimum, hence favoring a negative gross moist stability. It is argued that the asymmetry between the expanding and retreating phases of the winter Hadley cell is linked to the nonlinear seasonal evolution of near‐surface temperatures. Key Points: The location of the zero total energy transport (EFE) is a good ITCZ predictor on seasonal and longer time scales On subseasonal time scales, the EFE leads the ITCZ and the two do not always reside in the same hemisphere The gross moist stability of the Hadley circulation cannot be assumed as constant and can in fact become negative during the seasonal cycle